Supporting women with mild to moderate anxiety during pregnancy: the development of an intervention to be facilitated by midwives - Evans, Kerry (2018)
Aim: To develop an intervention that could be facilitated by midwives to improve symptoms of mild to moderate anxiety in pregnant women